The Traces of Religious Education in the Poem "Sebelum Nyawa Terlepas Raga" by Hartono "John Witir" - Nasution, Mutia; Ardian, Ade Rifani; Nasution, Mhd. Azhar (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
This article examines the poem “Sebelum Nyawa Terlepas Raga” by Hartono “John Witir” as a literary work that reflects spiritual and religious values, particularly in the context of awareness of the afterlife. This poem explicitly serves as an invitation for self-reflection on worldly arrogance that has the potential to distance individuals from God, as well as a warning about the dangers of pride that can cloud one’s conscience. This study aims to elucidate the religious educational ideology contained in the poem. Using a qualitative descriptive approach, the object of study is the poem ‘“Sebelum Nyawa Terlepas Raga” itself. The analysis was conducted by applying hermeneutic theory, utilising quotations from the poem that directly represent religious educational values. The data collection process involved three stages: collection, reduction, and presentation of data. Subsequently, the data were analysed descriptively to produce an accurate and comprehensive picture of the characteristics and interconnections of the elements under study. The findings of this study indicate that the poem “Sebelum Nyawa Terlepas Raga” by Hartono “John Witir” contains dimensions of religious relationships that include interactions between humans and God, humans and their fellow humans, and humans and themselves. Of these three forms of religious relationships, the relationship between humans and God is the most dominant aspect in this poem. Keywords: Poetry “Sebelum Nyawa Terlepas Raga”, Religious Education, Hermeneutics